Adsorption of lead ions from wastewater using nano silica spheres synthesized on calcium carbonate templates. Issue 11 (November 2020) - Manyangadze, Milton; Chikuruwo, Nyaradzai M.H.; Narsaiah, T. Bala; Chakra, Ch. Shilpa; Charis, Gratitude; Danha, Gwiranai; Mamvura, Tirivaviri A.
Abstract: Lead is a heavy metal that is bio accumulative and non-biodegradable that poses a threat to our health when it exists in excess in our bloodstream. It has found its way into wastewater from mostly chemical industrial processes. In this article, we investigated the adsorption and hence removal of lead (II) ions from wastewater in order to purify it for re-use in industrial processes or for plant and animal use. We synthesized nano silica hollow spheres (NSHS) and used them as adsorbents to remove lead ions from wastewater. When we characterized the NSHS using X-Ray diffraction, the amorphous nature of silica was evident with average crystal size of 39.5 nm. Scanning electron microscopy was used to determine the morphology of the adsorbent and the particles were found to be spherical in shape within a size range of 100–200 nm. Thermogravimetric analysis was used to determine the mass loss of NSHS which was ~2% at 800 °C. Our experimental results from adsorption studies showed that there was a linear relationship between temperature (27–60 °C) and adsorption efficiency and an inverse relationship between initial metal concentration (50–300 mg/L) and adsorption efficiency. At a maximum temperature of 60 °C and maximum initial metal concentration of 300 mg/L, the adsorption capacity was 200 mg/g and 262 mg/g, respectively while the adsorption efficiency was 99.6% and 87.4%, respectively. Our equilibrium and thermodynamic results revealed that the process was better modelled by the Langmuir adsorption isotherm (qmax = 266.89 mg/g and b = 0.89 L/mg). The adsorption process was both endothermic (ΔH = 97 kJ/mol) and spontaneous (ΔG = -22 kJ/mol). We can conclude that we were able to successfully synthesize NSHS, use them to remove lead (II) ions and the produced NSHS have a capacity that is higher than most other adsorbents investigated by other researchers. Abstract : Chemical Engineering; Environmental Science; Physical chemistry; Environmental Chemical Engineering; Adsorption; Surface Chemistry; Environmental Pollution; Nano sodium silicate hollow spheres; equilibrium studies; Freundlich isotherm; Langmuir isotherm; thermodynamic studies; Wastewater; lead ions.